CLINIC FOR PATIENTS WITH DENTURES COMPARATIVE DIAGNOSIS AND PATHOGENESIS - Axmedova Malika Qilichovna (TADQIQOTLAR.UZ, 2024)
Abstract: Many people have dental problems today is meeting Accordingly, in today's article, he used dental prostheses We will explain the clinical comparative diagnosis and pathogenesis of patients.